Design and development of an Autonomous Underwater Vehicle (AUV-FKEUTeM) - M. Shahrieel, M. Aras; H .A., Kasdirin; M. Herman, Jamaluddin; M. Farriz, Basar (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009 at MS Garden Hotel, Kuantan, Pahang, Malaysia.